The Development of Dual System Education in Vocational High School in Creating The School Autonomy - Pramono, R.; Rahman, Maman; Soesanto, Soesanto (Universitas Negeri Semarang, 2016)
The Role of Vocational High School (SMK) in preparing high school-skilled labors,is showing a less encouraging trend when viewed in terms of the number of competentgraduates. It is caused by several factors, low quality of human resources, infrastructure, curricula and learning method, education management and management operational support that is not optimal because it comes from city and state budgets. The purpose of this study is to find a dual system education development model in creating an autonomous school. This study was conducted at SMK in the city of Semarang which is projected to be national and international standard by taking sample of 8 SMK. Respondents in this study were 59 SMK teachers and 86 SMK students. Data collection technique is using enclosed questionnaire which include open questions. Analysis technique is using descriptive analysis. The study results shows that dual system education materials taught is not complete and not as desired. Many SMK yet have a clear roadmap about the development of dual system education in SMK. Low of networking with the industry causes the dual system education learning is not effective. This study propose an integrated model, so that SMK is able to produce graduates with high motivation and entrepreneurial skills.